EVALUATION OF THE EFFICIENCY OF THE SYSTEM OF TRANSPORT SERVICES FOR ENTERPRISES, TAKING INTO ACCOUNT REGIONAL AND TECHNOLOGICAL FEATURES. - Помазков, Михаил; Коваленко, Марина (SWorldJournal, 2021)
Metallurgical products are the first in the list of export goods of Ukraine. In an environment of competition, metallurgy operates when supply exceeds demand. Excess steel capacity remains in the world. According to various estimates, this is 2.2 billion